Pengaruh Naungan dan Ketinggian Tempat terhadap Produksi Pucuk Teh (Camellia sinensis L.) - Sakiroh Sakiroh; Kurnia Dewi Sasmita; Dwi Astutik (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Sakiroh S, Sasmita KD, Astutik, D. 2021. The impact of shade and altitude on tea shoots production (Camellia sinensis L.). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 209-218. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Tea plants are tropical and subtropical C3 plants. The increasing worldwide demand for tea has a significant impact on Indonesian tea demand. Tea production was observed with the application of appropriate technical culture. Tea plant production and productivity can be raised and maximized by considering the plant's physical and environmental characteristics. Shade plants have an impact on the tea plant's environments. Temporary shade plants include Crotalaria sp. and Tephrosia sp., whereas permanent shade plants contain Grevillea robusta. Temporary shade plants are those that are currently developing and require a light intensity of 65-70 percent to grow. When compared to not applying shade in the tea planting technique, shade can improve tea growth. Shades can offer several benefits, including lowering the temperature, increasing humidity, reducing light intensity of the leaves' surface, and lessening the effect of photoinhibition, Both of these factors would have a long-term impact on tea productivity. Upper leaves with shade had a 65 percent higher photosynthetic rate than leaves without shade. In both the dry and wet seasons, the productivity and production of shaded tea are higher than that of un-shaded tea. Tea productivity in the highlands is higher than tea productivity in the middle and lower regions.